Percutaneous mechanical support in catheter ablation of ventricular arrhythmias: hype or hope? - Kautzner, Josef; Hašková, Jana; Stojadinovič, Predrag; Peichl, Petr; Wichterle, Dan (Europace, 2024)
Catheter ablation (CA) has become an established treatment strategy for managing recurrent ventricular tachycardias (VTs) in patients with structural heart disease. In recent years, percutaneous mechanical circulatory support (PMCS) devices have been increasingly used intra-operatively to improve the ablation outcome. One indication would be rescue therapy for patients who develop haemodynamic deterioration during the ablation. However, more efforts are focused on identifying subjects who are at high risk of such deterioration and could benefit from the pre-emptive use of the PMCS. The third reason to use PMCS could be the inability to identify diffuse substrate, especially in non-ischaemic cardiomyopathy. This paper reviews available experiences using various types of PMCS in different clinical scenarios. Although PMCS allows mapping during VT, it does not significantly influence acute outcomes and not convincingly long-term outcomes. On the contrary, the complication rate appears to be higher in PMCS cohorts. Our data suggest that even in patients with severe left ventricular dysfunction, the substrate modification can be performed without the need for general anaesthesia and risk of haemodynamic decompensation. In end-stage heart failure associated with the electrical storm, implantation of a left ventricular assist device (or PMCS with a transition to the left ventricular assist device) might be the preferred strategy before CA. In high-risk patients who are not potential candidates for these treatment options, radiotherapy could be considered as a bail-out treatment of recurrent VTs. These approaches should be studied in prospective trials.
Keywords: Stereotactic arrhythmia radiotherapy; Substrate modification; Humans; Heart Failure; srdeční selhání; Risk Factors; rizikové faktory; Tachycardia, Ventricular; výsledek terapie; lidé; katetrizační ablace; podpůrné srdeční systémy; Treatment Outcome; Heart-Assist Devices; Percutaneous mechanical support; komorová tachykardie; hemodynamika; Hemodynamics; Catheter Ablation; Ventricular tachycardia; Catheter ablation